Distribución optima de rutas para camiones por el método húngaro. - Espinoza Velepucha, Erika Fernanda (My University, 2020)
The transport sector is one of the main participants in the economic development of a country, since without mobilization there is no trade. It is from the transport that the supply of merchandise exists at local, national and international level. There are many companies dedicated entirely to this trade, they are managed under their own jurisdictions respecting the laws and regulations that have been imposed for the operation of this type of company. The transport companies allocate their services to the transfer of materials used as raw material, processed products or the transfer of people. The objective of these companies is to provide the mobilization service to those who require it, obtaining profits from it; In addition, this group generates a large percentage of employment sources contemplated in the labor market. These companies must remain in constant innovation and training, in order to fully comply with the demands that arise every day in the market. This document proposes an exercise that must be solved based on the investigation of operations, in this example it is requested to establish the optimal routes that a group of 4 trucks must follow to obtain the maximum benefit. Whereas each route must be taken only by a single truck. Through research, we proceed to search for information that is useful to contextualize the problem and, based on a series of research methodologies, the information collected is processed, explaining the issues implicit in the proposed exercise.
El sector del transporte es uno de los principales participes en el desarrollo económico de un país, puesto que sin movilización no hay comercio. Es a partir del transporte que existe el suministro de mercancías a nivel local, nacional e internacional. Existen muchas empresas dedicadas enteramente a este oficio, se manejan bajo sus propias jurisdicciones respetando las leyes y reglamentos que se han impuesto para el funcionamiento de este tipo de compañía. Las empresas de transporte destinan sus servicios al traslado de materiales utilizados como materia prima, de productos elaborados o al traslado de personas. El objetivo de estas empresas es brindar el servicio de movilización a quienes lo requieran obteniendo ganancias a partir de ello; además, este grupo es generador un gran porcentaje de fuentes de empleo contempladas en el mercado laboral. Estas compañías deben mantenerse en constante innovación y capacitación, con tal de cumplir a cabalidad las exigencias que surgen día a día en el mercado. En este documento se propone un ejercicio que debe ser resuelto basándose en la investigación de operaciones, en este ejemplo se pide establecer las rutas optimas que deben seguir un grupo de 4 camiones para obtener el máximo beneficio. Considerando que cada ruta debe ser tomada únicamente por un solo camión. A través de la investigación se procede a buscar información que sea útil para contextualizar el problema y a partir de una serie de metodologías de investigación se procesa la información recaudada explicando así las temáticas implícitas en el ejercicio planteado.
Keywords: DESARROLLO ECONÓMICO; TRANSPORTE; RUTAS; MERCADO LABORAL